Isotope shifts of the 1s22s2p(J)−1s22s2 transition energies in Be-like thorium and uranium. (21st August 2019) - Zubova, N A; Anisimova, I S; Kaygorodov, M Yu; Kozhedub, Yu S; Malyshev, A V; Shabaev, V M; Tupitsyn, I I; Plunien, G; Brandau, C; Stöhlker, Th
Abstract: Precise calculations of the isotope shifts in berylliumlike thorium and uranium ions are presented. The main contributions to the field and mass shifts are calculated within the framework of the Dirac–Coulomb–Breit Hamiltonian employing the configuration-interaction Dirac–Fock–Sturm method. These calculations include the relativistic, electron–electron correlation, and Breit-interaction effects. The QED, nuclear deformation, and nuclear polarization corrections are also evaluated.